Estrés laboral y su relación en la calidad de atención del personal de enfermería del Hospital Básico Jaime Roldos Aguilera, octubre 2018 – abril 2019 - Contreras Rodríguez, Kimberly Yurlendy (2019)
INTRODUCTION: The present study was carried out at the "Jaime Roldós Aguilera" Basic Hospital in the city of Ventanas during the period October 2018 - April 2019 OBJECTIVE: our general objective is to determine the level of Work Stress and its relationship in the quality of care of the nursing staff of the Basic Hospital "Jaime Roldós Aguilera", METHODOLOGY: based on a cross-sectional descriptive study with a mixed quantitative and qualitative approach, two validated data collection instruments were used, the Malash Burnout Inventory for measure the level of stress in the nursing staff; and the CUCACE (Nursing Care Quality Questionnaire) to measure the quality of care from the patient's perception, the sample consisted of the 35 nursing professionals and 30 patients who were hospitalized in the corresponding areas of that institution who complied with it. the inclusion criteria established RESULTS: the results of the research indicate, according to the three dimensions studied, that 70% of the nursing staff showed a medium level of emotional exhaustion, 67% presented an average level of depersonalization, 53% reflected a level of low personal fulfillment; With respect to the quality of care evaluated from the patient's perspective, the data revealed that it is negative, meaning that they felt little satisfied in relation to the care received by the nursing staff. CONCLUSION: it was determined that after performing the analysis the nursing staff has been affected by stress and is directly related to the quality of care provided to the user.